Novel Homomorphic Encryption Scheme in Cloud Computing - Veena, C; M. Hanumanthappa, Dr (International Journal of Engineering and Technology, 2018)
Cloud computing is an indispensable technology for any business organization, such as banking, e-commerce, etc. Although technology has advantages in many areas; The protection of stored data is a major concern for all stakeholders in the architecture. Provide data security with respect to network security, control strategies and access to the service, data storage. Despite the efforts of service providers to build customer trust in data security, users need a passion for using technology for their business skills. Homomorphism coding is a data protection technique in which tasks can be performed on encrypted data themselves. In this article, we present an exploration of new homomorphism encryption methods with respect to data security and their use in cloud computing.Â Â